1993
DOI: 10.1086/468160
|View full text |Cite
|
Sign up to set email alerts
|

Self-Serving Assessments of Fairness and Pretrial Bargaining

Abstract: Each copy of any part of a JSTOR transmission must contain the same copyright notice that appears on the screen or printed page of such transmission.JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. The University of Chicago … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
2
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(140 citation statements)
references
References 0 publications
5
131
2
2
Order By: Relevance
“…Furthermore, unlike earlier research (e.g., Kruger, 1999;Loewenstein, Issacharoff, Camerer, & Babcock, 1993), we tested this assumption such that no extensive description of personal relevance was necessary. Thereby, we introduced a very subtle manipulation of personal relevance to the literature that may be conducive when conducting future research on this important subject.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unlike earlier research (e.g., Kruger, 1999;Loewenstein, Issacharoff, Camerer, & Babcock, 1993), we tested this assumption such that no extensive description of personal relevance was necessary. Thereby, we introduced a very subtle manipulation of personal relevance to the literature that may be conducive when conducting future research on this important subject.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Thompson and Loewenstein (1992) found that negotiators had self-serving conceptions of fairness and that such biases were related to the length of strikes during simulated negotiations. Indeed, studies have demonstrated that self-serving biases are evident among professional negotiators and that such biases are related to impasses (Loewenstein, Issacharoff, Camerer, & Babcock, 1993), length of strikes (Babcock, Wang, & Loewenstein, 1996), and reduced problem-solving and feelings of frustration (de Dreu, Nauta, & Van de Vliert, 1995). In summarizing this literature, Babcock and Loewenstein (1997) concluded that negotiators' tendencies to equate what is fair with what benefits themselves impedes negotiations by reducing the potential zone of agreement, by creating cynical perceptions of the other party, and by inflating perceptions of the minimum settlement point that is seen as fair.…”
Section: Self-serving Biases In Perceptionmentioning
confidence: 99%
“…Loewenstein et al (1993) created a highly realistic settlement scenario. They provided subjects (all students) with 27 pages of testimony from an actual accident case.…”
Section: Loewenstein and Babcockmentioning
confidence: 99%